2023
DOI: 10.1037/drm0000217
|View full text |Cite
|
Sign up to set email alerts
|

Bodily Self-Consciousness in Dreams Questionnaire (BSD-Q) and its relation to waking dissociative experiences.

Abstract: According to virtual reality dream theory , while dreaming, brains generate a dream world similar to a virtual reality environment, and this world uses the same predictive self/world modeling capacity as that used during wakefulness. The theory proposes that phenomenology of dreaming experience is based on the waking experience, a view widely accepted by dream researchers. In the current research, we argued that individuals with different intensities of dissociative experiences during waking, will report corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 118 publications
(179 reference statements)
0
1
0
Order By: Relevance
“…Prior studies have shown significant correlations when assessing characteristics of dreams with trait questionnaires and morning dream diaries within the same participants, especially in individuals who do not have poor dream recall 106 , 108 , 109 . Additionally, a number of studies have shown predictive validities in the use of trait dream questionnaires to predict individual differences in diverse outcomes such as aphantasia, olfactory experiences, and bodily self-consciouness 110 112 . Despite the limitations noted above, sampling dream content using a nightly awakening procedure would yield more accurate insights into the content of the dream itself, and would also make it feasible to compare dream content across different stages of sleep, an important feature of some theories of dreaming such as the NEXTUP theory 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown significant correlations when assessing characteristics of dreams with trait questionnaires and morning dream diaries within the same participants, especially in individuals who do not have poor dream recall 106 , 108 , 109 . Additionally, a number of studies have shown predictive validities in the use of trait dream questionnaires to predict individual differences in diverse outcomes such as aphantasia, olfactory experiences, and bodily self-consciouness 110 112 . Despite the limitations noted above, sampling dream content using a nightly awakening procedure would yield more accurate insights into the content of the dream itself, and would also make it feasible to compare dream content across different stages of sleep, an important feature of some theories of dreaming such as the NEXTUP theory 3 .…”
Section: Discussionmentioning
confidence: 99%